2014
DOI: 10.3224/zff.v26i1.15913
|View full text |Cite
|
Sign up to set email alerts
|

Berufliche Aufstiege im partnerschaftlichen Kontext – Zur Bedeutung von Homogamie und sozialer Unterstützung durch den Partner

Abstract: Based upon research on “coupled careers”, the partnership is seen as an important context where not only career opportunities but also barriers are generated. Using data from the Socio-Economic Panel Study (SOEP), this article pays particular attention to status homogamy and partners’ social support as beneficial aspects of partnerships for career advancement. The analysis of dual-earner couples reveals that men are more likely to move up into high occupational positions when they live in a highly qualified st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Janning (2006) has come to a similar conclusion for academic partnerships, where both partners work in the same occupation. Busch et al (2014) have found empirical evidence that for women there is a less pronounced effect of homogamy on promotion opportunities, whereas men in particular benefit from highly qualified homogameous partnership constellations.…”
Section: The Role Of Partners’ Resources In Partners’ Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Janning (2006) has come to a similar conclusion for academic partnerships, where both partners work in the same occupation. Busch et al (2014) have found empirical evidence that for women there is a less pronounced effect of homogamy on promotion opportunities, whereas men in particular benefit from highly qualified homogameous partnership constellations.…”
Section: The Role Of Partners’ Resources In Partners’ Supportmentioning
confidence: 99%
“…Other studies examined a partner's impact with a focus on occupational upward mobility. Studying promotions to high occupational positions in dual-earner couples, Busch, Bröckel, and Golsch (2014) have shown that, particularly for women, a partner's support with regard to career advancement is essential for gaining a high occupational position. For men, this effect only becomes evident if they are supported by their partner and other persons.…”
Section: Social Support Within Partnershipsmentioning
confidence: 99%
“…While emotional support becomes clear in the degree to which one partner shows understanding for the other partner's issues, instrumental support involves the provision of specific and concrete assistance. Instrumental support is often measured by the amount of housework done by the partner, while measures of emotional support typically capture a partner's empathy or emotional responsiveness to one's personal affairs (Busch, Bröckel & Golsch 2014). Beside these direct effects of emotional and instrumental support, both types can also have indirect effects, which go beyond the concrete situation of providing support and can cause sustainable positive outcomes for recipients of partner support (Shumaker & Brownell 1984).…”
Section: The Role Of Perceived Partner Supportmentioning
confidence: 99%
“…Dagegen finden sich für verhandlungstheoretische Modelle einige Belege: Zum einen die traditionalisierend wirkende Ehe aufgrund ihres vertrauensbildenden Charakters (Bernasco/Giesen 2000; Klaus/Steinbach 2002) und zum anderen der mit steigender weiblicher Erwerbserfahrung zurückgehende weibliche Anteil an der Hausarbeit (Bittman et al 2003;Brines 1994;Greenstein 2000;Haberkern 2007). Deutlich wird bei allen Untersuchungen, dass je nach Erwerbskonstellation unterschiedliche Reaktionen auf Veränderungen der Zuständigkeitsbereiche erkennbar sind und eine Berücksichtigung der unterschiedlichen Konstellationen daher nicht nur sinnvoll, sondern auch notwendig ist (Busch et al 2014;Evertsson/Nermo 2004;Gupta 2007;Haberkern 2007;Hochschild 1989;Mannino/Deutsch 2007).…”
Section: Theoretische Betrachtung Der Entscheidungssituationunclassified
“…Innerhalb der Neuen Haushaltsökonomie kann die Relation als Indikator für die derzeitige Spezialisierung gesehen werden, während sie bei der Verhandlungstheorie die aktuellen paarinternen Machtverhältnisse aufzeigt. Aus diesem Grund bedarf es bei der Untersuchung des Entscheidungsverhaltens über den Erwerbsumfang immer der Berücksichtigung bestehender Erwerbskonstellationen (für ähnliche Argumentationen siehe Busch et al 2014;Klaus/Steinbach 2002). In dieser Arbeit soll der Frage nachgegangen werden, wie Personen in Abhängigkeit vom Erwerbsumfang des Partners bzw.…”
Section: Introductionunclassified